MO919THE INTERPLAY BETWEEN IL-6 AND IL-17 MIGHT PLAY A SIGNIFICANT ROLE IN CHRONIC ANTIBODY MEDIATED REJECTION IN RENAL ALLOGRAFT RECIPIENTS. (29th May 2021) - Singh, Mantabya; Prasad, Narayan; Rai, Mohit; Jaiswal, Akhilesh Kumar; Behera, Manas Ranjan; Agarwal, Vikas; Misra, Durga P
Abstract: Background and Aims: Chronic antibody-mediated rejection (CABMR) plays a critical role in kidney allograft loss and consider among one of the most important barriers that is responsible for late term graft loss. Previously we believed that alloreactive T-cell and de-novo DSA responsible for late term graft loss but recent study suggested that not only immune cell, non-immune cells like fibroblast also plays important role in chronic inflammation and allograft rejection via IL-6 amplifier loop (IL-6+IL-17). The interaction between non-immune tissues/cells and the immune system plays a critical role in chronic inflammation and late graft rejection. In chronic inflammation IL-6 enhance the production of acute phase proteins, T cell Subset differentiation, Maturation of Plasma cells, Generation of cellular and humoral immune responses and Control the transition from acute to chronic inflammation by changing the nature of leucocyte infiltration (from neutrophils to monocyte). We sought to see whether IL-6 and IL-17A mediated synergistic activation of inflammation amplifier is operational in CABMR. Method: Recruitment of patients according to Banff 2017criteria and biopsy was taken from consented patients and establishment of fibroblast culture from renal biopsy of patients with CABMR. Fibroblast culture from CABMR patients were cultured to purity and pre stimulated with IL-6 (20ng/ µl), IL-17(50ng/ µl), IL-6 plus IL-17 for 24 hours and culture supernatant were collected for IL-6 ELISA to see synergistic activation. Serum IL-6, MCP1 and CCL20 levels of Healthy control (HC), CABMR and Non-CABMR patients and MCP1, CCL20 level in culture supernatant were measured by ELISA. m-RNA expression of IL-6, MCP1, CCL20 and SOCS3 gene were measured by real time PCR (Syber-green method) One-way ANOVA and Non-parametric Student t tests (two-tailed) were used for the statistical analysis of differences between groups. Results: In comparison to IL-6 and IL-17 alone these cytokines synergistically induced more IL-6 production from renal fibroblasts. ( Fig 1 ) also, we found that concentrations of effectors of inflammation amplifiers like IL-6, CCL-20 & MCP-1 in sera were significantly higher in CABMR patients compared to Non rejection patients, while their concentration in culture supernatant was higher when fibroblast cell stimulated with IL-6 and IL-17 together as compared either IL-6 or IL-17 alone. ( Fig 2 ) Gene expression analysis of IL-6, MCP1 and CCL20 was significant higher (p<0.001) with synergistic activation of IL-6 and IL-17 as compared to either IL-6 or IL-17 alone, while SOCS3 gene expression was downregulated. ( Fig 3 ) There was significant reduction in IL-6 concentration in culture supernatant with IL-6 and IL-17 inhibitor together ( Fig 4 ) and m-RNA expression of IL-6 and MCP-1 was significantly reduced. ( Fig 5 ) Conclusion: CABMR is perpetuated by inflammation amplifier loop or synergistic induction of IL-6 and IL-17. Inhibition of IL-6 with Anti-IL-6 (Tocilizumab) and IL-17 with Anti-IL-17 reduces the tissue injury marker (IL-6, MCP1, CCL20) and allograft rejection.